FAKTOR PENYEBAB ANAK PUTUS SEKOLAH - Abdul Hakim (LPPM Universitas Terbuka, 2020)
To improve the quality of human resources, the development of the education sector is very important.. Therefore, the Indonesian government has established a 12-year compulsory education program to create quality human resources. However, education participation at the secondary level needs to be increased, and the dropout rate needs to be controlled. This study uses secondary data from the March 2019 National Socio-Economic Survey (Susenas) to identify variables that affect the dropout rate for students ages 7 to 18 years in Aceh. In addition, the purpose of this study is to determine the probability of school dropouts by certain characteristics. The analysis used is logistic regression, which is a method that explains the relationship between the dichotomous response variable and a set of categorical explanatory variables. The result shows that the six variables selected were able to explain the variation of dropouts with a significance level of 5 percent. These variables are the education of household head, Kartu Indonesia Pintar/Program Indonesia Pintar (KIP/PIP) ownership, household size, working children, poverty, and urban-rural classification. The most dominant independent variable is ownership of KIP/PIP. Pembangunan di bidang pendidikan merupakan suatu hal yang sangat penting dalamm eningkatkan kualitas Sumber Daya Manusia. Oleh karena itu, pemerintah menetapkan program wajib belajar 12 tahun agar tercipta SDM yang berkualitas. Namun, partisipasi sekolah pada tingkat sekolah menengah perlu ditingkatkan agar angka putus sekolah dapat ditekan. Penelitian ini dilaksanakan di Provinsi Aceh menggunakan data Susenas Maret 2019 dengan tujuan mengidentifikasi variabel yang mempengaruhi angka putus sekolah pada usia 7–18 tahun. Selain itu, dapat juga untuk mengetahui probabilitas anak putus sekolah dengan karakteristik tertentu. Analisis yang digunakan adalah regresi logistik, yaitu suatu metode yang menerangkan hubungan antara variabel respon dikotomi dan satu set variabel penjelas katagori. Enam variabel yang dipilih mampu menjelaskan variasi anak putus sekolah dengan tingkat signifikan 5%. Variabel tersebut adalah pendidikan kepala rumah tangga, kepemilikan KIP/PIP, jumlah anggota rumah tangga, anak yang bekerja, kemiskinan, dan daerah tempat tinggal. Variabel yang paling dominan adalah kepemilikan KIP/PIP.